Influence of Duration and Temperature of Transport and Storage Prior to Processing on Cell Quality of Cord Blood Units - A German Experience - Strobel, Joachim; Brenner, Lukas; Zimmermann, Robert; Weiss, Dominik; Zingsem, Jürgen; Eckstein, Reinhold; Weisbach, Volker Günter (Clinical Laboratory, 2015)
In Germany, cord blood needs to be transported to the processing facility to be processed and cryopreserved within 48 hours after collection according to national guidelines. During that time, a temperature of 22 ± 4 degrees C must be maintained. The purpose of this study was to analyse the influence of temperature during transport and storage prior to processing and cryopreservation on stem cells in 2460 both autologous and allogeneic umbilical cord blood samples.Total and viable CD45+ cells, total and viable CD34+ cells, and mononuclear cells (MNC) of cord blood and resulting leucocyte concentrate both before and after freezing were analysed by flow cytometry. Transport protocols and the records of temperature measuring chips used in transport were evaluated in order to analyse how long each unit was exposed to which temperature ranges.On average, the cord blood preparations were delivered within 16.4 ± 6.3 hours. No cord blood was delivered and processed later than 48 hours after donation. Temperature of transport and storage before processing had minor but sometimes significant effects on cell viability. A temperature range of 20 - 24 degrees C showed best survival rates for CD34+ cells and highest colony forming potential.The temperature prior to processing has little yet sometimes significant effects on cell viability in stem cell concentrates prepared from cord blood. However, the absolute differences in cell viabilities are quite small. Therefore, the effect is clinically negligible in a range from 4 degrees C to 28 degrees C if cryopreservation is done within 48 hours.
EVALuna2:15998